RESEARCH ON FATIGUE TEST METHOD OF CAR BODY OF HIGH-SPEED EMU - WANG Chao; LIU ChaoTao; WU PingBo; SONG Ye; LI FanSong; ZHANG FuBing (Jixie qiangdu)
The vehicle body is an important bearing component of the high-speed train. The fatigue test can accurately evaluate the fatigue life of the vehicle body. It can also verify the accuracy of the simulation calculation model,and can take into account the incomplete technical considerations in the simulation analysis. This article compares the domestic and international relevant standards to determine the load of the vehicle body fatigue test of the high-speed EMU vehicle including the vertical direction of the vehicle body,the longitudinal load and the lateral load of the center pin,and the longitudinal load of the coupler,and formulates the fatigue of the vehicle body according to the test load. The test plan was completed and the fatigue test of the entire vehicle body of the first high-speed EMU in China was completed. Fatigue test found that the weld hook inside the ribbed plate weld existed hidden dangers of fatigue and put forward an optimized program. The optimized scheme was further verified.Finally,the fatigue life of the body of the high-speed EMU was proved to meet the design requirements.